Examining the Relationship Between Attachment Styles and Marital Conflicts with the Mediating Role of Intimacy Styles in Couples Applying for Divorce - Tayebi , Toktam; Vatankhah, Hamidreza; Jadidi , Hooshang (Mental Health and Lifestyle Journal, 2026)
The objective of the present study was to examine the relationship between attachment styles and marital conflicts with the mediating role of intimacy styles in couples applying for divorce. This study employed a descriptive–correlational design using structural equation modeling. The statistical population consisted of 500 individuals (250 couples) applying for divorce who referred to the Dispute Resolution Councils of Tehran Province in 2025. Participants were selected using convenience sampling. Data were collected using the Revised Adult Attachment Scale, the Marital Intimacy Scale, and the Kansas Marital Conflict Scale. The reliability of the instruments was confirmed using Cronbach’s alpha coefficients (attachment styles = 0.863, intimacy styles = 0.742, marital conflicts = 0.801). Data analysis was conducted using SPSS and AMOS (Version 24). Model fit was evaluated using multiple indices including CFI, GFI, NFI, RMSEA, and CMIN/DF. The structural model demonstrated acceptable fit (CMIN/DF = 1.439, CFI = 0.980, GFI = 0.972, NFI = 0.980, RMSEA = 0.030). Attachment styles had a significant direct effect on intimacy styles (β = 0.298, p < 0.001) and marital conflicts (β = 0.230, p < 0.001). Intimacy styles exerted a significant negative effect on marital conflicts (β = −0.255, p < 0.001). The indirect effect of attachment styles on marital conflicts through intimacy styles was significant (β = 0.075, p = 0.001), confirming partial mediation, with a total effect coefficient of 0.305. The findings indicate that intimacy styles play a critical mediating role in the relationship between attachment styles and marital conflicts, underscoring the importance of addressing attachment-related emotional processes and enhancing intimacy in interventions aimed at reducing marital conflict among couples seeking divorce.